2005
DOI: 10.2174/1385272053544380
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the Electrochemistry of Some Nitro Compounds of Biological Significance

Abstract: The redox chemistry of different nitro compounds of biological significance is focused to understand how the reduction of the nitro group can play an active role in several aspects as: electroanalytical determinations, free radical generation and stability and free radical reactivity. We have focused our studies to a lot of pharmaceuticals belonging mainly to the following families: calcium antagonists as nitrobenzene substituted 1,4-dihydropyridines, antibacterial and anti protozoan agents as nitroimidazoles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
84
2
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 85 publications
7
84
2
10
Order By: Relevance
“…chloro, fluoro, difluoromethyl, and trifluoromethyl) or an electron-releasing group (i.e. methyl and methoxy) onto the conjugated quinoxaline ring have been reported in previous studies [7,12,13,14,16,17,18]. The present study correlates well with these earlier reports on the structural effects on potential.…”
Section: Relationship Between Electrochemical Behavior and Structuresupporting
confidence: 92%
See 1 more Smart Citation
“…chloro, fluoro, difluoromethyl, and trifluoromethyl) or an electron-releasing group (i.e. methyl and methoxy) onto the conjugated quinoxaline ring have been reported in previous studies [7,12,13,14,16,17,18]. The present study correlates well with these earlier reports on the structural effects on potential.…”
Section: Relationship Between Electrochemical Behavior and Structuresupporting
confidence: 92%
“…In this publication, we have demonstrated that our quinoxaline derivatives affect the mitochondrial dehydrogenase activity [6]. Therefore, electrochemistry plays an important role when studying the formation of this radical species and its reactivity in one-pot systems [7]. The purpose of the present study was to investigate the electrochemical properties of a series of quinoxaline-di-N-oxide-2-ketone derivatives, and determine the possible relationship between their reduction potentials, their structure and their anti-chagasic activity.…”
Section: Introductionmentioning
confidence: 99%
“…For this, a convenient experimental condition ͑aprotic medium, mixed solvents, alkaline-pH medium͒, in which the low disponibility of protons favors the R-NO 2 •− kinetic stability, is necessary. 11 Under such conditions, the electrochemical behavior of NF has been extensively studied by using working electrodes such as mercury, [12][13][14][15] gold, 14 glassy carbon, 14,16 and boron-doped diamond. 17,18 The molecular modification has been the most promising approach to introduce drugs in therapeutics and to obtain better drugs.…”
mentioning
confidence: 99%
“…[28][29][30][31] In the first pathway (Equation (4) and (5)), reversible formation of one-electron nitro radical anion is followed by irreversible three-electron reduction. As the stability of ArNO 2 · is increased by the absence of In the second possible pathway (Equation (6) and (7)), four-electron reduction of NO 2 to NHOH (Equation (6)) and two-electron reduction of NHOH to NH 2 (Equation (7)) takes place.…”
Section: Electrochemical Behavior Of Aclonifen and The Influence Omentioning
confidence: 99%